Role of Endogenous Hormones in Gender Determination in Casuarina equisetifolia - Shanthi, A.; Warrier, Rekha R. (Indian Forester, 2018)
Endogenous levels of phytohormones like auxin, gibberellins, cytokinin, abscisic acid and ethylene appear to determine the fate of flower sex. In higher levels of auxins, cytokinins and ethylene have been found to be correlated with female sex expression whereas a greater amount of gibberellins favors the differentiation of male sex organs. There are three types of plants in regard to sexuality: those in which male and female flower are born on separate (dioecious), those that bear male and female flower on same plant (monoecious) and those in which male and female organs are born together in same plant. Three types of sexual patterns are exists (male, female and monoceious) in Casuarina equisetifolia. Hence we attempted to study the role of endogenous hormones such as auxins and gibberellins in Casuarina equisetifolia to determine its genders . This study was carried out to screen four types of clonal samples such as male, female, monoceious and inconstant. The results from the study revealed that higher levels of IAA have been found to be correlated with female sex expressions whereas a greater amount of gibberellins favors the differentiation of male sex organs. Phenotypic expression of flower sex is controlled by a balance between male and female promoting hormones.